Calling Your Name: Sebuah Metode Penggunaan Papan Nama Sebagai Dorongan Motivasi Belajar dan Refleksi Diri: [Penelitian Tindakan Kelas Mata Kuliah Komunikasi Bisnis dan Ilmu Administrasi Bisnis] - Nurachmah, Asri Essada; Utami, Dian Gita; Samsinar (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
This article describes action research in the form of the use of nametags that trigger students' motivation and their self-awareness in the classroom. The study was conducted by identifying classes through two stages of the PDAC cycle and also by conducting direct observations, interviews and questionnaires with fifty nine students in the communication classes at Business Administration Study Program PNUP. The results showed that by using nametags in the class, students felt more enthusiastic, more valued as individuals, willing to contribute more, figured-out their strength and weakness during class interactive session, and self-reflect on the learning process. The research aims to provide alternative solution regarding class action to be more productive and adaptive to student characters in which coherent with the UN Sustainable Development Goals number 4 quality of education and number 12 collaboration to achieve goals.